Work-family policy trade-offs for mothers? Unpacking the cross-national variation in motherhood earnings penalties - Michelle J. Budig; Joya Misra; Irene Boeckmann (Work and occupations, 2016)
Recent scholarship suggests welfare state interventions, as measured by policy indices, create gendered trade-offs wherein reduced work–family conflict corresponds to greater gender wage inequality. The authors reconsider these trade-offs by unpacking these indices and examining specific policy relationships with motherhood-based wage inequality to consider how different policies have different effects. Using original policy data and Luxembourg Income Study microdata, multilevel models across 22 countries examine the relationships among country-level family policies, tax policies, and the motherhood wage penalty. The authors find policies that maintain maternal labor market attachment through moderate-length leaves, publicly funded childcare, lower marginal tax rates on second earners, and paternity leave are correlated with smaller motherhood wage penalties.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; family; women; earnings; social policy